Жадьылӥсь мешок: выжыкылъёс / Вениамин Ившин - Ившин Вениамин Никонорович (Удмуртия, 2012)
Экземпляры: (20141119) / Инвентарный номер: 38059 / Цена: 91.25 / Сис.шифр: С(Удм) / Авт.знак: И 25 / ГРНТИ: 17 / ББК: 84(2Рос=Удм)